Política de segurança da informação: uma estratégia para garantir a proteção e a integridade das informações arquivísticas no Departamento de Arquivo Geral da UFSM - Sfreddo, Josiane Ayres (2012)
Presents a study on information security in order to propose an Information Security Policy for the Department of General Archives (DAG), Federal University of Santa Maria (UFSM) as a way of enabling the protection, availability and secure access to archival information (not digital), in the university context. It is characterized as an exploratory qualitative approach, assuming a case study form, because it involves the study of a certain subject allowing its wide and detailed knowledge. It was first conducted a more detailed study of the Standard ISO/IEC 27002 which is a code of practice for information security, providing guidelines for the implementation of an Information Security Policy, based on regulations according to the institutional purposes. The study aimed, at first, to adapt the requirements and controls present in this standard archival context, focusing on the protection of not digital information, a research in the Heritage Documentary line. Thus, the adaptation of the standard for archival followed the structure of the original standard, seeking to provide for the archival institutions a tool to subsidize the development of an Information Security Policy, providing a more secure and reliable protection. In order to compose this policy a data collection was carried out through interviews, structured within questions about security information, based on the standard ISO/IEC 27002, on the previous study and the Adaptation of the Standard for the archival context. With the data collected and analyzed, along with the DAG, it can be verified that the problems causer of threats to the security of not digital archives in the department are directly related to the lack of security to the perimeter and to the absence of a physical control, including entries and exits. These security actions made it possible, together with the adaption of the standard, to propose control in order to prevent further incidents. This way it was possible to structure the Document of the Security Policy representing the materialization of the Security Policy according to the needs presented by DAG. This document will serve as an instrument to support and guide employees, users and third parties in the conduct of institutional activities. However, it is up to the department to approve it and implement it for the purpose of preventing incidents, thereby providing safe reliable and continuous access to not digital information by him guarded.